Incidence of aphids in different traps on potato in Gangetic plains of West Bengal (The Journal of Plant Protection Sciences, 2020)
A field experiment was conducted during rabi season of 2006-07 and 2007- 08 at Adisaptagram Block Seed Farm, Hooghly, West Bengal to evaluate the population dynamics of aphids with the help of yellow pan trap and yellow sticky trap. The population of aphid catches was quite lower in yellow pan trap than yellow sticky trap. Aphids were first observed in traps during third week of December and the population of pests gradually increased to reach the peak in second week of February in the first year of study (2006-07) while in second year of study (2007-08) the aphid population appeared in second week of December and attained its peak by the end of February. The abiotic factors viz., temperature (maximum & minimum), relative humidity% (maximum & minimum) and bright sunshine hour had significant effect on aphid population. The same abiotic factors were quite different between the first and second year. This was due to the fact that the climatic conditions in second year varied distinctly from the first year.
Keywords: Potato; traps; aphids; Gangetic; plains; West Bengal